CD133 Antigen as a Potential Marker of Melanoma Stem Cells: In Vitro and In Vivo Studies - Tomasz Kloskowski; Joanna Jarząbkowska; Arkadiusz Jundziłł; Daria Balcerczyk; Monika Buhl; Kamil Szeliski; Magdalena Bodnar; Andrzej Marszałek; Gerard Drewa; Tomasz Drewa; Marta Pokrywczyńska (Stem Cells International)
Melanoma is the most dangerous type of skin cancer. Cancer stem cells (CSCs) are suspected to be responsible for the cancer recurrence and in the consequence for cancer therapy failure. CD133 is a potential marker for detection of melanoma CSCs. Experiments were performed on the B16-F10 mouse melanoma cell line. CD133+ cells were isolated using an immunomagnetic cell sorting technique. After isolation proliferative and clonogenic potential of CD133+, CD133- and CD133+/- were evaluated. The potential of CD133+ and CD133- cells for tumor induction was conducted on C57BL/6J mouse model. Three different cell quantities (100, 1000, 10000) were tested. Tumor morphology, number of mitoses, and tumor necrosis area were analyzed. Average 0.12% CD133+ cells were isolated. Compared to CD133- and unsorted CD133+/- cells, CD133+ cells were characterized by the higher proliferative and clonogenic potential. These properties were not confirmed in vivo, as both CD133+ and CD133- cells induced tumor growth in mouse model. No statistical differences in mitosis number and tumor necrosis area were observed. Simultaneous detection of CD133 antigen with other markers is necessary for accurate identification of these melanoma cancer stem cells.